(untitled) (The Research of Medical Science Review, 2025)
Background: Women across the globe express concerns about the well-being of their partners and children, often playing a pivotal role in shaping reproductive attitudes and decisions on contraceptive use. Notably, Pakistan is experiencing a higher growth rate (1.8%) compared to other nations, potentially making it the most populous country in the world in the coming years. Objectives: To assess the utilization and evaluate the factors which influence the utilization of family planning services among female of reproductive age. Methods: Descriptive cross sectional was conducted in tertiary care hospital, lady Atchison Hospital Lahore. Data was collected from the study participants with help of questionnaire. Data were analyzed with the help statistical tests chi-square using p less than 0.05 Result: Most of the participants (99.1%) were married, most of the participants (38.4%) were married from 1-5 years, (43.8%) women having interval between the child was 2 years and the (42.9%) were having 3 to 4 children. This is concluded that (33.0%) women don’t know about the family planning methods and (36.6%) women having no awareness about family planning methods. This is concluded that mass media highlights only (15.2%) about the awareness and learning regarding family services in the population. (26.8%) population knows about family planning methods and their sexual effects. Conclusion: Some of the participants knowing about family planning methods. reasons were; they face hurdles like low income, limited awareness of available methods, and reluctance to discuss family planning. Their unfavorable attitudes contribute to moderate utilization rates and discontinuation of methods. The study emphasizes the need for comprehensive education, economic empowerment, and community engagement tailored to address socio-economic and cultural barriers in promoting family planning acceptance and utilization.